-3ab + 3ab
-3ab + 3ab
Taking ab as a common in above term, we get
- 3ab + 3ab = ab( -3 + 3)
Simplify above term, we get
- 3ab + 3ab = ab(0)
Our solutions are written by experts, many with advanced degrees, and available 24/7See Solution
Q: Use the One-to-One Property to solve the equation for x. ex2-4 = e3x
A: Refer to the question,According to one to one property of exponents if bases are same, af(x) = ag(x)...
Q: Give the domain and range of the quadratic function whose graph is described. The vertex is (-1,-5) ...
A: Given information:The vertex is (-1,-5) and the parabola opens up.
Q: Find the coordinates of the vertex of the quadratic function: y=x2+3
A: The quadratic equation is given by,
Q: Solve for x: 3x+1 = 27
A: The equation is given by,
Q: (x+9)/8 = 5/4 +(x-3)/2
A: To calculate the value of x from the provided equation which is shown below,
Q: Why is rounding a number important?
A: Rounding is a way of simplifying a number to make that easier to understand and work with.Moreover i...
Q: Use the graph of y f(x) to graph the function g(x)=f(x)-2 Choose the correct graph of g below y fox)...
A: g(x)=f(x)-2 means the graph will move 2 units down.
Q: Solve and graph the solution on a number line: x-3>1
A: We are given an inequality as
Q: Determine whether each proportion is true or false. 27) 8/10 = 2/5/2
A: The given proportion is 8/10=2/5/2.It can be written as 8:10=2:5/2.
Sorry about that. What wasn’t helpful?